SISTEM INFORMASI INVENTORY STOK BARANG PADA TOKO NONO AKSESORIS BERBASIS WEBSITE - Martinus Rafael (2022)
Inventory data system is a system that is made to identify the amount of inventory. Not only that, using a good inventory system will reduce the risk of inventory being lost or stolen. In its application, the Nono Accessories Store is a trading business with a lot of sales and purchase data as well as inventory, which in the end is not stored systematically, because the store is still recording manually. The purpose of this study was to analyze the use of the Stock Inventory System with the research method used to design this Stock Inventory using the waterfall method. The author does this design using HTML and CSS languages on website pages as well as PHP programming language and uses a XAMPP server then MYSQL to help store data, it is hoped that this system can handle the work of inputting Stock Inventory data quickly and accurately and can be updated easily.